Informing the UK Muslim Community on Organ Donation Evaluating the Effect of a National Public Health Programme by Health Professionals and Faith Leaders - Ali, Omar M. E.; Gkekas, Eleftherios; Ali, Ahmad M. S.; Tang, Tsz Yau Tiffany; Ahmed, Sameer; Chowdhury, Imadul; Waqar, Salman; Hamed, Amer; Al-Ghazal, Sharif; Ahmed, Saeed (2023)
There is a significant shortage of transplantable organs in the UK particularly from Black, Asian and Minority Ethnic (BAME) groups, of which Muslims make a large proportion. The British Islamic Medical Association (BIMA) held a nationwide series of community gatherings with the aim of describing the beliefs and attitudes to organ donation amongst British Muslims and evaluate the efficacy of a national public health programme on views and uncertainties regarding religious permissibility and willingness to register. Eight public forums were held across the UK between June 2019 and March 2020 by the British Islamic Medical Association (BIMA). A panel of experts consisting of health professionals and Imams discussed with audiences the procedures, experiences and Islamic ethico-legal rulings on organ donation. Attendees completed a self-administered questionnaire which captured demographic data along with opinions before and after the session regarding religious permissibility and willingness to register given permissibility. A total of 554 respondents across seven UK cities were included with a M:F ratio 1:1.1. Only 45 (8%) respondents were registered as organ donors. Amongst those not registered multiple justifications were detailed, foremost of which was religious uncertainty (73%). Pre-intervention results indicated 50% of respondents were unsure of the permissibility of organ donation in Islam. Of those initially unsure or against permissibility or willingness to register, 72% changed their opinion towards deeming it permissible and 60% towards a willingness to register indicating a significant change in opinion (p < 0.001). The effectiveness of our interventions suggests further education incorporating faith leaders alongside local healthcare professionals to address religious and cultural concerns can reduce uncertainty whilst improving organ donation rates among the Muslim community.
Keywords: Asian and minority ethnic (BAME); Black; Faith; Inequalities; Muslim; Organ Donation; Transplantation; United Kingdom